THE PROBLEMS AND OBSTACLES OF COMPETENCY DEVELOPMENT OF PERSONAL ASSISTANTS - Trakoonsantirat , Wipapan; Ratchathawan , Kwannapis (Journal of MCU Nakhondhat, 2023)
This article was a part of the research, aimed to study 1) problems and obstacles of competency development of personal assistants (PA) and suggestions of competency development of personal assistants. The research used Research and Development Methodology with Semi - structure interviews. 7 Groups of key informants had been interview in Loei, Mukdahan, Roi-et, Buriram, Ubon Ratchathani, Yasothon, including the director and officer of department of empowerment of persons with disabilities. Research findings found that the problems and obstacles of personal assistants’ competency development consist of the difference of development way between workshop and on-the-job training, the obstacle from online training; training period: some informants reflect too long period, but others feel incompletely practice; lack of activities during spread of the epidemic; inconvenient transportation; the difference of content and field practice; and communication & coordination problems. For suggestions, consist of 1) Human resource development-oriented regarding types and ways of development: upskilling and reskilling; on-site and online training; experience sharing between personal assistants; field trips with network; media preparation to facilitate personal assistant’s self-development; the contents of developments consist of coordinating for fund raising, career development, using convenient format for performance report writing; empowering the roles of trainers to local agency; expanding the audience and qualifying the trainees; post-training monitoring. 2) Human resource management-oriented; increasing in numbers of personal assistants, compensations and benefits. 3) Management-oriented; personal assistants’ database preparation for service management of people with disabilities.